2022
DOI: 10.1101/2022.04.29.489992
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Shock or jump: deimatic behaviour is repeatable and polymorphic in a yellow-bellied toad

Abstract: Inter-individual variation in antipredatory strategies has long attracted curiosity among scientists. Deimatisms is a complex and time-structured antipredatory strategy consisting in prey suddenly unleashing unexpected defences to frighten predators and stop their attack. Being deimatism traditionally considered as a stereotyped antipredatory response, the inter-individual variation in phenotypic traits related to deimatic displays is almost unexplored. In this study, we employed common garden experiments on 7… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 42 publications
0
5
0
Order By: Relevance
“…Both deimatic behavior and aposematism can utilize bright coloration; indeed, deimatism may be an evolutionary precursor of aposematism (Loeffler‐Henry et al., 2023). For example, the long exposure of the conspicuous ventrum of several amphibian species upon disturbance has been historically thought of as aposematism (Wells, 2007) but is now being considered as deimatic behavior (Chiocchio et al., 2023). One crucial difference is that although deimatic behavior may vary greatly in the performance duration, its main goal is to “trigger an unlearned avoidance response in the attacker” (Drinkwater et al., 2022, p. 4), whereas aposematism is often, but not always, displayed to enhance the avoidance learning process in the attacker.…”
Section: Improving Conceptual Understandingmentioning
confidence: 99%
See 1 more Smart Citation
“…Both deimatic behavior and aposematism can utilize bright coloration; indeed, deimatism may be an evolutionary precursor of aposematism (Loeffler‐Henry et al., 2023). For example, the long exposure of the conspicuous ventrum of several amphibian species upon disturbance has been historically thought of as aposematism (Wells, 2007) but is now being considered as deimatic behavior (Chiocchio et al., 2023). One crucial difference is that although deimatic behavior may vary greatly in the performance duration, its main goal is to “trigger an unlearned avoidance response in the attacker” (Drinkwater et al., 2022, p. 4), whereas aposematism is often, but not always, displayed to enhance the avoidance learning process in the attacker.…”
Section: Improving Conceptual Understandingmentioning
confidence: 99%
“…indeed, deimatism may be an evolutionary precursor of aposematism (Loeffler-Henry et al, 2023). For example, the long exposure of the conspicuous ventrum of several amphibian species upon disturbance has been historically thought of as aposematism (Wells, 2007) but is now being considered as deimatic behavior (Chiocchio et al, 2023).…”
Section: Deimatic Behaviormentioning
confidence: 99%
“…With this study, we aim at providing genomic resources to investigate the genetic underpinnings of inter-individual behavioral differences in warning signals. We generated the first de novo brain transcriptome of a species showing polymorphism in behavioral traits associated with deimatic displays, the Apennine yellow-bellied toad Bombina pachypus 12 . The yellow-bellied toads of the genus Bombina are textbook examples of unken-reflex, a deimatic behavior which consists in toads arching their body and exposing their aposematically colored ventral side.…”
Section: Background and Summarymentioning
confidence: 99%
“…Experimental evidence has shown within-population variation in the way B. pachypus toads reacted to predation stimuli: about half of the toads quickly reacted with a long and intense body arching and aposematic display (i.e. the unken-reflex), while the other half of the individuals analysed did not show deimatic behavior, but rather moved away 12 . These two antipredatory strategies have been proposed to reflect the way individuals cope with environmental challenges, i.e.…”
Section: Background and Summarymentioning
confidence: 99%
“…prolonged unken-reflex display vs no unken-reflex display (thereafter referred as "+" and "-", respectively). Behavioral profiles were scored as in Chiocchio et al 12 : 3 toads showed prolonged unken-reflex (+), whereas the other 3 did not show unken-reflex (-), as reported in Table 1. Sampling procedures were approved by the Italian Ministry of Ecological Transition and the Italian National Institute for Environmental Protection and Research (ISPRA; permit number: 20824, 18-03-2020).…”
Section: Sample Collection and Rna Preparationmentioning
confidence: 99%